2012
DOI: 10.1269/jrr.11131
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Displacements of the Clips in Surgical Cavity for External-beam Partial Breast Irradiation after Breast-conserving Surgery Based on 4DCT

Abstract: To explore the clip and the geometrical center displacements based on the four-dimensional computed tomography (4DCT) for external-beam partial breast irradiation (EB-PBI), fourteen breast cancer patients treated with breast-conserving surgery were recruited for EB-PBI and undertook 4DCT simulation during free breathing. The displacements of the selected clips and the geometrical center at left-right (LR), anterior-posterior (AP) and superior-inferior (SI) directions were measured. The comparison and the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Of the 19 studies, surgical clips and gold fiducial markers were used as references in measuring the displacements in 11 studies. In this study, the 3D displacements of selected clips were similar to those in previous studies [17,23]. Based on 4D-CT, Wang et al [17] reported that the intrafraction displacements in the LR, AP and SI directions were 0.460.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Of the 19 studies, surgical clips and gold fiducial markers were used as references in measuring the displacements in 11 studies. In this study, the 3D displacements of selected clips were similar to those in previous studies [17,23]. Based on 4D-CT, Wang et al [17] reported that the intrafraction displacements in the LR, AP and SI directions were 0.460.…”
Section: Discussionsupporting
confidence: 88%
“…The displacement magnitude of the clip COM in this study was similar to the results acquired by Wang et al [17], who applied 4D-CT to explore the displacement for EB-PBI and reported that the displacements of the geometric (consisting of all the surgical clips) centre in the LR, AP and SI directions were 1.460.4, 2.06 1.0 and 1.961.0 mm, respectively. We found that in the 3D directions, the similar displacements of the clip COM were significantly larger than those of the GTV c , GTV s , GTV c1s .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations